Plasmon enhanced perovskite-metallic photodetectors. (15th January 2021) - Gu, Qiongchan; Hu, Chunhai; Yang, Jiming; Lv, Jiangtao; Ying, Yu; Jiang, Xiaoxiao; Si, Guangyuan
Abstract: Perovskite based photodetectors and hybrid devices possess distinctive properties which have enabled considerable practical applications since perovskite is an ideal candidate for higher sensitivity and response speed. In this work, an elegant approach of fabricating hybrid photodetectors based on perovskite-metallic nanostructures is shown. By combining gold triangle nanoantennae with a CH3 NH2 PbI3 film, a simple yet effective fabrication method of hybrid organic-inorganic perovskite photodetectors with improved performanceis experimentally demonstrated. Finite difference time domain calculations agree well with experimental results. Perovskite-assisted devices are highly attractive due to their unique properties and the results shown in this work may find extensive potential applications for novel flexible photodetectors and other related optical devices. Graphical abstract: Unlabelled Image Highlights: A hybrid photodetecting system is experimentally demonstrated and characterized. This device exhibits higher photocurrent due to enhanced electric field of plasmonic arrays. The measured external quantum efficiency is 12.6% at 450 nm wavelength.